1989
DOI: 10.1007/bf00915033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of event rate and display time on sustained attention in hyperactive, normal, and control children

Abstract: Two experiments were conducted to determine whether hyperactive boys have a unique deficit in sustained attention. Groups with DSM-III diagnoses of attention deficit disorder (ADDH), conduct disorder (CD), ADDH + CD, and learning disorder were compared with normal controls on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 28 publications
9
97
0
Order By: Relevance
“…These results support the validity of the narrowly defined syndrome of pervasive hyperactivity rather than that of the more broadly defined ADDH diagnosis (see also Chee et al, 1989;Sandberg et al, 1978;Schachar et al, 1981;Taylor et al, 1986). At the same time, deficient inhibitory control cannot simply be attributed to the severity of disturbance: The mixed ADDH + CD group had the greatest number of symptoms of psychopathology yet did not have the most severe deficit in inhibitory control.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…These results support the validity of the narrowly defined syndrome of pervasive hyperactivity rather than that of the more broadly defined ADDH diagnosis (see also Chee et al, 1989;Sandberg et al, 1978;Schachar et al, 1981;Taylor et al, 1986). At the same time, deficient inhibitory control cannot simply be attributed to the severity of disturbance: The mixed ADDH + CD group had the greatest number of symptoms of psychopathology yet did not have the most severe deficit in inhibitory control.…”
Section: Discussionsupporting
confidence: 64%
“…At the same time, deficient inhibitory control cannot simply be attributed to the severity of disturbance: The mixed ADDH + CD group had the greatest number of symptoms of psychopathology yet did not have the most severe deficit in inhibitory control. This is the second experiment in which we have observed that the ADDH + CD group does not demonstrate the same cognitive deficit as the ADDH group (Chee et al, 1989). Differences between these two subgroups have also appeared in studies of their clinical features.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, as ISI becomes longer, behavioural activation declines (Sanders, 1998). In several studies it has been shown that performance of AD\HD children is impaired when a long ISI or preparatory interval is used (Zahn, Kruesi, & Rapoport, 1991), or long delays between cue and target (Swanson et al, 1991 ;Tomporowski, Tinsley, & Hager, 1994), long preresponse delays (Sonuga-Barke & Taylor, 1992), and slow event rates (Chee, Logan, Schachar, Lindsay, & Wachsmuth, 1989 ;Conte, Kinsbourne, Swanson, Zirk, & Samuels, 1986 ;Van der Meere, Shalev, Bo$ rger, & Gross-Tsur, 1995 ;Van der Meere, Stemerdink, & Gunning, 1995 ; Van der Meere, Vreeling, & . The typical slow and variable response style of 348 A. SCHERES, J. OOSTERLAAN, and J.…”
Section: Introductionmentioning
confidence: 99%